(untitled) (Docentes 2.0 Journal, 2025)
The implementation of the New Mexican School (NEM) has generated a shift in education. However, its impact on high school mathematics learning has been understudied despite the profound modifications made. Therefore, this study aimed to analyze students’ perceptions of changes in the teaching of this area of ??the discipline. It is framed within the humanistic paradigm, employing a hermeneutic method that focuses on the qualitative, utilizing an interpretive-descriptive and cross-sectional case study design. To this end, an open questionnaire was administered to the entire second-semester population (141 subjects) of a public high school in Veracruz. The analysis was based on data mining, a categorization and analysis technique that allowed for the identification of thematic patterns in the responses. Participants perceived greater contextualization of the content and a more practical orientation in their academic and professional training. They also noted difficulties in organizing the content and adapting teaching methodologies. Findings suggest the need to identify areas for improvement in the teaching of mathematics within this new educational model.